X-linked competition — implications for human development and disease - Boone, Philip M.; Buenaventura, Teresa; King, James W. D.; Merkenschlager, Matthias (Nature reviews. Genetics, 2025)
During early mammalian female development, X chromosome inactivation leads to random transcriptional silencing of one of the two X chromosomes. This inactivation is maintained through subsequent cell divisions, leading to intra-individual diversity, whereby cells express either the maternal or paternal X chromosome. Differences in X chromosome sequence content can trigger competitive interactions between clones that may alter organismal development and skew the representation of X-linked sequence variants in a cell-type-specific manner — a recently described phenomenon termed X-linked competition in analogy to existing cell competition paradigms. Skewed representation can define the phenotypic impact of X-linked variants, for example, the manifestation of disease in female carriers of X-linked disease alleles. Here, we review what is currently known about X-linked competition, reflect on what remains to be learnt and map out the implications for X-linked human disease. Differences in X chromosome sequence content can trigger competitive interactions between clones that may alter organismal development and skew the representation of X-linked sequence variants in a cell-type-specific manner. The authors review this recently described phenomenon of X-linked competition and map out the implications for X-linked human diseases.